PENERAPAN SISTEM INFORMASI MANAJEMEN SUMBER DAYA MANUSIA (HRIS) DALAM MENINGKATKAN KINERJA ORGANISASI: SEBUAH TINJAUAN LITERATUR SISTEMATIS - Dwi Putri; Vicky Brama Kumbara (Ensiklopedia of Journal, 2026)
Human Resource Information Systems (HRIS) — known in Indonesia as Sistem Informasi Manajemen Sumber Daya Manusia (SIM-SDM) — have become a key component that helps organizations manage employee records, run administrative processes, and support decisions related to human resources. This study was carried out to systematically map how the adoption of HRIS shapes organizational performance at both the administrative and strategic levels. It follows a Systematic Literature Review (SLR) design built around the PRISMA stages of identification, screening, eligibility assessment, and synthesis, drawing on articles published from 2006 to 2025 across Google Scholar, Garuda, SINTA, and DOAJ. An initial pool of 212 articles was narrowed down to 20 that satisfied the inclusion criteria and were examined thematically. Five recurring themes emerged from the synthesis: automation of HR administration, support for recruitment and performance management, the strategic role of HRIS in HR decision-making, its effect on organizational performance, and the factors and obstacles shaping successful implementation. Overall, the review indicates that HRIS adoption tends to bring positive gains for administrative efficiency and organizational performance, though its strategic value is only fully unlocked when paired with readiness among staff, backing from senior management, and sufficient training in using the system. It is hoped that these results can guide both scholars and HR practitioners in shaping more effective HRIS adoption strategies.Keywords: human resource information system; HRIS; organizational performance; systematic literature review